PENERAPAN NEW MEDIA TECHNOLOGY PADA TELEVISI BERBASIS INTERNET SOLOPOS TV (2013-2015) - Didik Haryadi Santoso; Heri Budianto (Jurnal Visi Komunikasi, 2016)
Solopos.tv is present as an internet-based television as an alternative to virtual audiences in the present era. How to develop internet based television program in solopos.tv? The question becomes a common thread in this paper. This research use case study method. The core of the discussion is divided into four namely; (1) Human resources (2) Information management is content production process and content distribution (3) Facilities, infrastructure and funding and (4) Internet-based television structure and culture. The conclusions of this paper are: First, Internet-based television has a difference with conventional television is usually from the use of human resources are trimmed so that it can reduce production costs and post production. Second, the management of informative content not only in the content production process but also its virtual based distribution strategy. The sophistication of new media technology helps save production costs and post production. Finally, the lean structure and creative culture so that it produces creative programs because it supports young people who are familiar with virtual digital technology. Solopos.tv hadir sebagai televisi berbasis internet sebagai alternatif bagi para audien virtual di era kekinian. Bagaimana pengembangan program televisi berbasis internet di solopos.tv? Pertanyaan tersebut menjadi benang merah dalam tulisan ini. Penelitian ini menggunakan metode studi kasus. Inti pembahasan terbagi menjadi empat yaitu; (1) Sumber daya manusia (2) Pengelolaan informasi yaitu proses produksi konten dan distribusi konten (3) Sarana, prasarana dan pendanaan dan (4) Struktur dan kultur televisi berbasis internet. Simpulan dari tulisan ini yaitu: Pertama, televisi berbasis internet memiliki perbedaan dengan televisi konvensional biasa yaitu dari sisi penggunaan sumber daya manusia yang dipangkas sehingga dapat memperkecil biaya produksi dan pasca produksi. Kedua, pengelolaan konten informatif tidak hanya pada proses produksi konten namun juga strategi pendistribusiannya yang berbasis virtual. Kecanggihan teknologi new media membantu menghemat biaya produksi dan pasca produksi. Terakhir, struktur yang ramping dan kultur yang kreatif sehingga berhasil memproduksi berbagai program kreatif karena didukung anak muda yang akrab dengan teknologi digital virtual.